The effects of aquatic exercise on body composition and nonspecific low back pain in elderly males - Taheri, Morteza; Irandoust, Khadijeh (Journal of Physical Therapy Science, 2015)
[Purpose] The purpose of this study was to investigate the effect of aquatic exercises on nonspecific low back pain (LBP) in elderly males. [Subjects and Methods] Thirty-two elderly men aged 65 or older were recruited and randomly allocated to two groups: aquatic training (3 d/wk for 12 wk) or a control group. Body mass index (BMI), percentage of body fat (PBF), waist-hip ratio (WHR), and trunk muscle mass were measured before and after training. [Results] The results suggested that all obesity variables including BMI, WHR, and PBF of the aquatic training group were decreased significantly, while the trunk muscle mass of the aquatic training group was increased significantly. Furthermore, low back pain was decreased in the subjects after the intervention. [Conclusion] The water-based program improved LBP and body composition in the elderly men.